Students of Social Work in the Slipstream of the Politics of Activation: Results of Explorative Studies. - Bernd Dollinger; Nina Oelkers; Holger Ziegler (Social Work & Society, 2013)
The relationship between the body politic and social work has never been without tensions. The most recent developments in the body politic towards attitudes of "social activation" do nothing to help the relationship. "Social activation" concentrates and has a focus on a structure of negative sanctions, controlling clients and axiomatic aims - especially in relation to integrating people into the workforce. In this context, non-conditional support is increasingly discredited. Currently it is unknown in which way professional social workers share these attitudes. Based on explorative surveys, in this article we will state why it is necessary to further examine those attitudes. Using the results of 3 surveys of attitudes in students of social work and one study of the attitudes of social workers working in child and youth welfare, it is shown that there are a large amount of "welfare critics" and punitive attitudes to be found. Despite the fact this is a comparatively small sample, it seems from these results that social workers are not predisposed to develop friendly or sympathetic relationships or attitudes towards their clients. Increasingly it seems that at least some of the students have developed restrictive and disciplinary attitudes towards clients that are similar to current tendenciesin the politics of social activation.